Revealing the economic value of managed aquifer recharge: Evidence from a contingent valuation study in Italy. Issue 8 (4th August 2017) - Damigos, D.; Tentes, G.; Balzarini, M.; Furlanis, F.; Vianello, A.
Abstract: Managed aquifer recharge [MAR) is a promising water management tool toward restoring groundwater balance and securing groundwater ecosystem services (i.e., water for drinking, industrial or irrigation use, control of land subsidence, maintenance of environmental flows to groundwater dependent ecosystems, etc.). Obviously, MAR projects can improve the quality of lives of the people by several ways. Thus, from a social perspective, the benefits of MAR cannot and should not be based only on market revenues or costs. Although the value of groundwater, from a social perspective, has been a subject of socio‐economic research, literature on the value of MAR per se is very limited. This paper, focusing on Italy which is a country with extensive utilization of MAR, aims to estimate the economic value of MAR and makes a first step toward filling this gap in the literature. For this purpose, the Contingent Valuation method was implemented to provide a monetary estimate and to explore the factors influencing people's attitude and willingness to pay for MAR. The results show that society holds not only use but also significant nonuse values, which are a part of the total economic value (TEV) of groundwater according to related research efforts. To this end, MAR valuation highlights its social importance for groundwater conservation and provides a solid basis for incorporating its nonmarket benefits into groundwater management policies and assessments. Key Points: A contingent valuation study was conducted in Italy to estimate the economic value of managed aquifer recharge The total economic value that society attaches to managed aquifer recharge is significant though lower than that of groundwater The society holds nonmarket values for managed aquifer recharge that should be incorporated into groundwater management policies